Contemporary Chinese politics : new sources, methods, and field strategies - Carlson, Allen, 1968- (New York : Cambridge University Press, 2010)
'Contemporary Chinese Politics: Sources, Methods, and Field Strategies considers how new and diverse sources and methods are changing the study of Chinese politics. Contributors spanning three generations in China studies place their distinct qualitative and quantitative methodological approaches in the framework of the discipline and point to challenges or opportunities (or both) of adapting new sources and methods to the study of contemporary China. How can we more effectively use new sources and methods of data collection? How can we better integrate the study of Chinese politics into the discipline of political science, to the betterment of both? How can we more appropriately manage the logistical and ethical problems of doing political research in the challenging Chinese environment? In addressing these questions, this comprehensive methodological survey will be of immense interest to graduate students heading into the field for the first time and experienced scholars looking to keep abreast of the state of the art in the study of Chinese politics'--
State-generated data and contentious politics in China / Xi Chen -- Why archives? / Neil J. Diamant -- The central committee, past and present: a method of quantifying elite biographies / Victor Shih, Wei Shan and Mingxing Liu -- Experimental methods and psychological measures in the study of Chinese foreign policy / Peter Hays Gries -- Internet resources and the study of Chinese foreign relations: can cyberspace shed new light on China's approach to the world? / Allen Carslon and Hong Duan -- Information overload? Collecting, managing, and analyzing Chinese media content / Daniela Stockman -- The worm's-eye view: using ethnography to illuminate labor politics and institutional change in contemporary China / Calvin Chen -- More than an interview, less than Sedaka: studying subtle and hidden politics with site-intensive methods / Benjamin L. Read -- Cases, questions, and comparison in research on contemporary Chinese politics / William Hurst -- A survey of survey research on Chinese politics: what have we learned? / Melanie Manion -- Surveying prospects for political change: capturing political and economic variation in empirical research in China / Bruce J. Dickson -- Using clustered spatial data to study diffusion: the case of legal institutions in China / Pierre F. Landry -- Measuring change and stability over a decade in the Beijing area study / Mingming Shen and Ming Yang with Melanie Manion -- Quantitative research and issues of political sensitivity in rural China / Lily L. Tsai -- Reflections on the evolution of the China field in political science / Kenneth Lieberthal
Includes bibliographical references and index
Keywords: Political science -- Methodology; China -- Politics and government -- 2002-; China -- Politics and government -- 2002- -- Methodology